Women and distance higher education: rural and urban experiences in the post-pandemic - Edith J. Cisneros-Cohernour; José Gabriel Domínguez Castillo; Ileana del Socorro Vázquez Carrillo (Universidad de Guadalajara, 2024)
During the covid-19 pandemic, distance education witnessed a surge in credibility, popularity, and advantages; however, this change disproportionately impacted vulnerable groups: the low-income population, the disabled, indigenous groups and children of migrants. While research in basic education has been conducted, information regarding online learning experiences of female university students is limited, especially in relation to gender. Therefore, the present study surveyed 1 206 female undergraduate students from rural and urban contexts to analyze their experiences in distance classes during confinement. Significant differences were found according to context, with women from urban settings valuing the design of assignments and strategies, and instructional design, while those from rural contexts demanded greater attention from their tutors. In both cases, participants lacked prior experience with online courses and suitable learning environments. In conclusion, these disparities warrant further investigation and targeted measures to bridge the gender gap in distance education